1999
DOI: 10.1016/s0378-1097(99)00506-6
|View full text |Cite
|
Sign up to set email alerts
|

Cellular localization of a Hsp90 homologue in Porphyromonas gingivalis

Abstract: We previously reported an association between elevated serum antibody titers to the 90-kDa human heat shock protein (Hsp90), periodontal health and colonization by Porphyromonas gingivalis. In this study, we examined the cellular localization of the Hsp90 homologue of P. gingivalis. Cultures of P. gingivalis were heat-stressed (45³C) and examined for localization of the Hsp90 homologue. Heat stress induced a 4^5-fold increase in anti-Hsp90 antibody reactivity over that of the unstressed controls. Western blot … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…This association appears to be protective only in individuals with P. gingivalis in their subgingival dental plaque (22). Subsequently, we reported that P. gingivalis expressed a 68-kDa protein reactive with antibodies directed against human Hsp90 (21). The antibody reactivity and the presence of a 68-kDa polypeptide are consistent with the existence of a member of the HtpG family, the Hsp90 homologue found in prokaryotes.…”
mentioning
confidence: 59%
See 2 more Smart Citations
“…This association appears to be protective only in individuals with P. gingivalis in their subgingival dental plaque (22). Subsequently, we reported that P. gingivalis expressed a 68-kDa protein reactive with antibodies directed against human Hsp90 (21). The antibody reactivity and the presence of a 68-kDa polypeptide are consistent with the existence of a member of the HtpG family, the Hsp90 homologue found in prokaryotes.…”
mentioning
confidence: 59%
“…This antibody was raised against a conserved epitope of A. ambisexualis shown to react with multiple species (33). Two additional antibodies subsequently became available for use in the analysis of P. gingivalis Western blots: rabbit anti-E. coli HtpG, a generous gift of James Bardwell, and rabbit anti-human Hsp90 prepared in our laboratory (21). Reactivity with P. gingivalis ATCC 33277 whole cells at mid-log phase (A 600 ϭ 0.32) stressed at 45°C or held at a control temperature of 37°C is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lopatin et al (1999a) found a 68-kDa HSP90 protein in P. gingivalis that cross-reacts with antibodies to human HSP90. They also reported the presence of antibodies in the sera of periodontitis patients that cross-react with P. gingivalis HSP90 (Lopatin et al, 1999b).…”
Section: (33) Hsp90 Proteinsmentioning
confidence: 97%
“…These molecules seem to provide protection from only a very high level of heat shock (ϳ45°C) and are involved in tetrapyrrole biosynthesis (51). HtpG of P. gingivalis is minimally expressed on the bacterial surface, and an HtpG disruption mutation in P. gingivalis did not affect growth or adherence to mammalian cells (26,47). The N-terminal 600 amino acids of HtpG contain some regions common to all molecules of the HSP90 group; however, P18 was found to be exclusive to Bacteroides spp.…”
mentioning
confidence: 99%